Sorption equilibrium and kinetics for cyclohexane, toluene, and water on Athabasca oil sands solids. (11th January 2016) - Tan, Xiaoli; Vagi, Lisa; Liu, Qi; Choi, Phillip; Gray, Murray R.
ABSTRACT: The sorption of solvents from the vapour phase to solid substrates is important in producing heavy oil and bitumen, particularly from the oil sands. We investigated the sorption and desorption equilibrium and kinetics of cyclohexane, toluene, and water on kaolinite, fine solids, and organic‐rich fine solids isolated from Athabasca oil sands over a wide range of solvent vapour concentrations using a gravimetric method. The isotherms for both adsorption and desorption of solvent vapour were determined, and the Brunauer‐Emmett‐Teller equation was used to fit the experimental data. The initial kinetic rate constants for the adsorption and desorption of solvent vapour were determined with the linear driving force model. The results were compared and discussed in terms of the type of solvent, the content of organic materials, and the surface area of the solid substrates. The results suggest that, in addition to the adsorption of solvent on mineral surfaces, the contribution from solvent partitioning in the organic materials and the porosity resulting from high amounts of organic materials are significant factors for solvent uptake and kinetic rate constants. In mixed solvent vapours, the competitive sorption of water and cyclohexane was observed in the solid substrates. However, the degree of competitiveness decreased with an increase in the content of organic materials in the substrates.